2013
DOI: 10.1002/ijc.28556
|View full text |Cite
|
Sign up to set email alerts
|

Progression of carcinogen‐induced fibrosarcomas is associated with the accumulation of naïve CD4+ T cells via blood vessels and lymphatics

Abstract: The tumor microenvironment comprises newly formed blood and lymphatic vessels which shape the influx, retention and departure of lymphocytes within the tumor mass. Thus, by influencing the intratumoral composition of lymphocytes, these vessels affect the manner in which the adaptive immune system responds to the tumor, either promoting or impairing effective antitumor immunity. In our study, we utilized a mouse model of carcinogen‐induced fibrosarcoma to examine the composition of tumor‐infiltrating lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
(58 reference statements)
2
13
0
Order By: Relevance
“…We then showed that naive CD4 + T cells from the PB of breast cancer patients differentiate in vitro into functional Tregs by exposure to autologous DCs and CM from their tumors. Although migration of naive T cells to peripheral lymphoid organs is mediated by CCL19 and CCL21 30 , migration of these cells to tumors is independent of these chemokines 31 . We implicated CCL18, previously identified as a breast cancer TAM-secreted chemokine 21,24 , in recruiting naive CD4 + T cells into breast tumors by binding to the chemokine receptor PITPNM3.…”
Section: Discussionmentioning
confidence: 99%
“…We then showed that naive CD4 + T cells from the PB of breast cancer patients differentiate in vitro into functional Tregs by exposure to autologous DCs and CM from their tumors. Although migration of naive T cells to peripheral lymphoid organs is mediated by CCL19 and CCL21 30 , migration of these cells to tumors is independent of these chemokines 31 . We implicated CCL18, previously identified as a breast cancer TAM-secreted chemokine 21,24 , in recruiting naive CD4 + T cells into breast tumors by binding to the chemokine receptor PITPNM3.…”
Section: Discussionmentioning
confidence: 99%
“…T cells also enter via aberrantly formed blood and lymphatic vessels (47). It is thought that Tregs become enriched within the TIL pool through selective proliferation and retention within the tumor microenvironment (48).…”
Section: Discussionmentioning
confidence: 99%
“…This results in a net leakage of plasma into the interstitium that, if unchecked, causes fluid imbalance and tissue swelling. To resolve this mass transport problem, which is on the order of ~3 L of excess filtered blood plasma per day (12), the lymphatic system provides a drainage conduit (Figure 1) (13, 14) that, by virtue of cyclic pressure gradient variations (15), imparts a convective driving force for the removal of excess fluid from the interstitium. Thus, fluids and small molecules from interstitial tissues that drain into the lymphatic capillary plexus are concentrated as lymph (16, 17) and convected via the pumping function and valve-segmented lymphangion structure of larger lymphatic vessels to draining lymph nodes in a unidirectional fashion.…”
Section: Immune Physiology Of Lymphatic Transportmentioning
confidence: 99%
“…( b ) Microstructures of skin-draining lymph nodes with ( left ) normal, ( middle ) impaired, and ( right ) tumor lymphatic transport are shown immunohistochemically and schematically, emphasizing representative collagen organization, T and B cell segmentation, and high endothelial venule (HEV) remodeling responses. Modified from References 4, 10, 13, and 14 with permission.…”
Section: Figurementioning
confidence: 99%